1996
DOI: 10.1093/humrep/11.suppl_2.35
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial vasculature in Norplant(R) users: preliminary results from a hysteroscopic study

Abstract: Long-acting progestogenic contraceptives are frequently associated with disturbances of menstrual bleeding patterns. In particular, irregular, frequent and prolonged bleeding are commonly seen. The mechanism of this irregular bleeding is unknown, but changes in the endometrial vasculature are thought to be of importance. In endometrial biopsies from Norplant users, an increase in endometrial microvascular density has been observed after 3-12 months. Morphological changes in endometrial capillaries following pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…BTB is thought to arise from superficial vessels within the endometrium which increase in number and fragility in Norplant users (Hickey et al 1996, Hickey & Fraser 2002. We also observed substantial changes in BV in the mouse model.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…BTB is thought to arise from superficial vessels within the endometrium which increase in number and fragility in Norplant users (Hickey et al 1996, Hickey & Fraser 2002. We also observed substantial changes in BV in the mouse model.…”
Section: Discussionsupporting
confidence: 54%
“…These include an increase in number and size of small endometrial blood vessels (BV) as well as an increase in microvascular fragility , Hickey et al 1996, Pritts et al 2005. Increased BV density was observed in the endometrium of women recently exposed to Norplant; however, the number of BV was not indicative of increased bleeding or spotting (Hickey et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Important hysteroscopic investigations of women complaining of BTB with both low and high dose progestogens have shown that bleeding occurs focally in the endometrium and originates from superficial, dilated vessels [23]. These vessels were also prone to contact bleeding during hysteroscopy.…”
Section: Endometrial Vasculaturementioning
confidence: 99%
“…In Norplant users, these vessels appear dilated and thin walled (Hickey et al 1996) and are increased in number in women with prolonged bleeding (Hickey & Fraser 2002). Furthermore, vessel support is decreased as observed by a decrease in perivascular smooth muscle a-actin .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated numbers of some leukocyte populations and expression of matrix degrading enzymes, the matrix metalloproteinases, will also contribute to tissue fragility (Vincent et al 2002). Although the blood arises from the fragile blood vessels, it is clear that epithelial integrity must also be disturbed for vaginal bleeding to occur (Hickey & Fraser 2002) and indeed, sheets of easily detached surface epithelium are often seen at hysteroscopy (Hickey et al 1996) in users of P-only contraceptives, suggesting that the epithelium is fragile.…”
Section: Introductionmentioning
confidence: 99%